THE EFFECTIVENESS OF ETHNOMATHEMATICS-BASED LKPD DEVELOPMENT IN IMPROVING MATHEMATICAL LITERACY - Yuslia Fendy, Livi Eka; Mariana, Neni; Ekawati, Rooselyna (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This research development aims to test the feasibility of ethnomathe-matics-based student worksheets as an improvement of mathematics literacy in elementary schools. Validation testing was carried out by media experts, material experts, peers and trials with 3 stages including individual, small group trials and large groups. This student worksheet can be accessed online by sharing a link via WhatsApp, this student worksheet can be made easily, interactively, and cheaply because the researcher made it from the Canva application which is integrated with the youtube platform. This type of development research uses Research and Development with the ADDIE development model. The target of this research is grade V students of SD Negeri Sidokumpul Sidoarjo. Based on the results of the validation of media experts from the digital-based student worksheet, it got an average of 92.6%, while the results of the validation of the material experts got an average score of 90%. The results of the feasibility test from peers received a good response with an average of 90.4%, followed by a one-on-one (individual) test with an average result of 90%, in small group testing an average of 87%, and in large group testing with an average of 88%. Based on the validation from experts and the trials that have been carried out, ethnomathemat-ics-based student worksheets as an improvement of mathematical literacy are feasible and effective to be used in the learning process.